Infections and antibiotic use in early childhood have limited importance in developing manifest type 1 diabetes – The ABIS cohort study - Bélteky, Malin; Wahlberg, Jeanette; Ludvigsson, Johnny (Frontiers in Endocrinology, 2025)
AimsTo investigate the effect of early childhood infections and antibiotic use on the risk of type 1 diabetes in a general population cohort.Research Design and MethodsThe All Babies In Southeast Sweden (ABIS) cohort followed 16 428 children from birth. Questionnaires collected at 1 year (n=11 093), 3 years (n=8 890) and 5 years of age (n=7 445) included data on infections and antibiotic use and were validated against national registers. After a mean follow-up of 25 years, 168 individuals have been diagnosed with type 1 diabetes (1.0% of the original cohort, aged 1-24.5 years).ResultsThere were few significant differences in type or frequency of early childhood infections or antibiotic use between cases with type 1 diabetes and the reference group (remaining individuals who did not develop type 1 diabetes) after adjusting for sex, heredity and socioeconomic status. A small number of type 1 diabetes children (4.8% compared to 0.8% of the reference group) reported six or more episodes of gastroenteritis in the 1-3-year age group, resulting in an adjusted odds ratio (aOR) of 8.21; 95% CI 2.70-25.01, p<0.001. Cases of type 1 diabetes with an increased genetic risk (n=91) reported fewer episodes of the common cold between 1 and 3 years of age compared to the reference group (aOR 0.27; 0.13-0.58, p<0.001). Individuals with type 1 diabetes without risk-associated HLA alleles (n=14) reported a higher frequency of pneumonia in the 1–3- and 3–5-year age group (aOR 26.08; 6.29-108.17, p<0.001 and aOR 35.63; 4.10-309.96, p=0.001 respectively), and had more viral and total infections registered in the National Patient Register from 0-5 years (aOR 5.72; 1.59-20.57, p=0.008 and aOR 18.71; 1.95-179.55, p=0.01).ConclusionsChildhood infections could increase the risk of developing type 1 diabetes in a small group of individuals without risk-associated HLA alleles, but this was not seen in the majority with HLA-risk. More research is required for this overlooked population, including screening and prevention trials. The association to frequent gastrointestinal infections in the first years of life needs to be reproduced in other studies to be confirmed.